Midgut volvulus secondary to congenital malrotation in an adult with Ladd’s band: a case report - Bhatta, Bijay Raj; Shrestha, Samrat; Shakya, Niliza; Shrestha, Mecklina; Thapa, Kaushal Samsher (International Surgery Journal, 2024)
Adult midgut volvulus is a rare surgical disease, with an estimated incidence of less than 0.15%, and more common in Asia and Africa as compared to Europe and the US. It is a developmental anomaly characterized by failure to complete normal fetal rotation of the midgut around the Superior Mesenteric Artery (SMA) inside the peritoneal cavity. Though rare, adult midgut volvulus has the potential for bowel ischemia-related complications, and thus clinicians should have a reasonable index of suspicion to diagnose this. Early computed tomography (CT) scan with diagnostic accuracy of more than 83% would help in early recognition and management of these rare causes of intestinal obstruction. In this study, we reported the case of an adult primary midgut volvulus in a 30-year-old male who presented with features of acute bowel obstruction with a history of similar recurrent episodes and renal transplant. Diagnosis of midgut volvulus was made based on contrast-enhanced CT findings, and Ladd’s procedure was performed.